The equine nurse's approach to arthroscopic surgery: part 2 – care and maintenance of arthroscopy equipment. Issue 1 (23rd December 2020) - Ryan, Jackie; Johnson, Jessica P.
ABSTRACT: The equine veterinary nurse plays a crucial role in the care and set-up of equipment for arthroscopic procedures. In this Part 2 of a 3-part series, we will provide a practical resource for equine nurses, covering aspects such as cleaning and disinfection of instrumentation, equipment care, and set-up for arthroscopic surgery in the horse.